Cross-Cultural Pragmatic Failure From the Perspective of Politeness - Mami, Ibtisam H.; Attaweel, Radia A. ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2018)
The present paper attempts to outline the importance of familiarity of the politeness phenomenon amongst the fifth and seventh semester students of English Department, Misurata University and elaborate its influence on the socio-cultural attitudes and values in different contexts. It focuses on the teachability of pragmatic aspects of English in regard to the speech acts of requests and apologies from the perspective of politeness in the classroom in order to foster the students’ awareness of the phenomenon of politeness and the appropriate strategies according to the context. It also intends to explore the types of strategies of requests and apologies which they use in their English productions and to discover whether there are any significant differences between students’ requests and apologies strategies with respect to their academic levels. The participants are a total of (48) students from two different levels in the English Department. It was found out that students were not aware of the direct relation between language and the phenomenon of politeness. The results indicated that there were no significant differences between students’ requests and apology strategies and their academic levels. The results also revealed the teachability of English pragmatic aspects of both requests and apologies which has led to raising the students’ pragmatic ability in producing polite requests and apologies.